Researching the older consumer - Kiddle, Janet (Henry Stewart Talks, 2009)
Researching the older market, Age of respondent, Physical effects of ageing, Social class of respondent, Health of respondent, Internet penetration, When and where to conduct research, Implications for qualitative research, Implications for quantitative research, Case studies